A comparison of fluorescent Ca2+ indicators for imaging local Ca2+ signals in cultured cells. Issue 6 (December 2015) - Lock, Jeffrey T.; Parker, Ian; Smith, Ian F.
Graphical abstract: Highlights: We evaluated multiple Ca 2+ sensitive dyes to image local Ca 2+ signals. Cal-520 is the best performing green-emitting dye. Rhod-4 is the best performing red-emitting dye. GCaMP6 protein sensors are not suitable for imaging local Ca 2+ signals. Abstract: Localized subcellular changes in Ca 2+ serve as important cellular signaling elements, regulating processes as diverse as neuronal excitability and gene expression. Studies of cellular Ca 2+ signaling have been greatly facilitated by the availability of fluorescent Ca 2+ indicators. The respective merits of different indicators to monitor bulk changes in cellular Ca 2+ levels have been widely evaluated, but a comprehensive comparison for their use in detecting and analyzing local, subcellular Ca 2+ signals is lacking. Here, we evaluated several fluorescent Ca 2+ indicators in the context of local Ca 2+ signals (puffs) evoked by inositol 1, 4, 5-trisphosphate (IP3 ) in cultured human neuroblastoma SH-SY5Y cells, using high-speed video-microscopy. Altogether, nine synthetic Ca 2+ dyes (Fluo-4, Fluo-8, Fluo-8 high affinity, Fluo-8 low affinity, Oregon Green BAPTA-1, Cal-520, Rhod-4, Asante Calcium Red, and X-Rhod-1) and three genetically-encoded Ca 2+ -indicators (GCaMP6-slow, -medium and -fast variants) were tested; criteria include the magnitude, kinetics, signal-to-noise ratio and detection efficiency of local Ca 2+ puffs. Among these, we conclude that Cal-520 is the optimal indicator for detecting and faithfully tracking local events; that Rhod-4 is the red-emitting indicator of choice; and that none of the GCaMP6 variants are well suited for imaging subcellular Ca 2+ signals.